ELECTRONEUROMYOGRAPHY EXAMINATION OF DIABETIC POLYNEUROPATHY PATIENTS - Nurlaela, Siti; Kurniawan, Shahdevi Nandar; Husna, Machlusil (Malang Neurology Journal, 2019)
Background: Diabetic polyneuropathy (DPN) is one of the chronic complications that occur in approximately 80% of diabetes mellitus (DM) patients. This condition is a results of metabolic, vascular, and immunological disorders.Objective: To determine the profile of electroneuromyography (ENMG) examination of DPN patients at neurology clinic of Saiful Anwar General Hospital.Methods: This cross-sectional observational descriptive study was carried out at Saiful Anwar General Hospital Malang from June 1, 2015 to December 31, 2015, with purposive sampling method. A total of 43 DM patients with symptoms of polyneuropathy fulfilling inclusion criteria and no exclusion criteria were examined for ENMG. ENMG examirnation were including distal latency, amplitude and nerve conduction velocity of 4 motoric nerves (median, ulnar, tibial, peroneal) & 3 sensory nerves (median, ulnar, sural), and F waves of ulnar, median and peroneal nerves of the left and right extremities.Results: Of the 43 patients evaluated in this study, the mean sensory sural nerve conduction velocity was 13.01 m/s. The majority type of nerve damage in diabetic polyneuropathy patients in this studywere mixed type (52.33% in the median nerve, 60.47% in the ulnar nerve, 72.10% in the tibial nerve, and 54.65% in the peroneal nerve in motor nerve studies and 80.23% in the median nerve and 88.37% in the peroneal nerve in the sensory nerve studies).Conclusion: The nerve damage that occurs in DPN patients at Saiful Anwar general Hospital is severe, with the majority being the axonal demyelinating type, especially in the sensory nerve fibers in the inferior extremities.